[PP.17.36] MEMBRANE EFFECT ON RATE CARDIAC MARKER IN ALGERIAN HAEMODIALYSIS PATIENTS. (September 2017) - Arab, M.; Zenati, A.; Haddouche, D.; Labou, N.; Rayane, T.; Guechi, Z.
Abstract : Objective: Actually, 14000 haemodialyzed patients are awaiting for a transplant organ in Algeria. Cardiovascular complications are the main cause of death in haemodialyzed patients with high mortality risk with regard to general population. The hs (cTnT) high sensitive troponine T is a cardiac biomarker for the diagnosis of the acute myocardial infarction, NTproBNP is marker of heart failure. However, its rate are high in haemodialyzed patients objective Study of the membrane effect in the variation rate of hs cTnT and NT proBNP Design and method: This is an observational and prospective study. We conducted a study on 90 asymptomatic patients who undergoing chronic haemodialysis 51 men and 39 women. In these patients, predialysis and postdialysis circulating concentration of hs cTnT and NTproBNP were measured by electrochemiluminescence method Elecsys 2010 Roche Diagnostics. Results: All of our patients showed higher levels hs cTnT and NT proBNP greater than physiological value on predialysis and postdialysis. No significant difference was found by Mann Whiteney test p > 0, 05. Conclusions: Our study confirms that the hs cTnT and NTproBNP rate are frequently high in chronic haemodialysis. Dialysis membrane has no influence on the hs cTnT and NTproBNP rate; For that matter, it is recommanded to determine an individual value in this population that might be taken as a reference value for monitoring this population.